Economic hardships in adulthood and mental health in Sweden. the Swedish National Public Health Survey 2009 - Ahnquist Johanna; Wamala Sarah P (BMC, 2011)
Abstract Background Possible accumulative effects of a combined economic hardship's measure, including both income and non-income related economic hardships measures, on mental health has not been well investigated. The aim of this paper was to investigate; (i) independent associations between multiple measures of economic hardships and mental health problems, and (ii) associations between a combined economic hardships measure and mental health problems. Methods We analysed data from the 2009 Swedish National Survey of Public Health comprising a randomly selected representative national sample combined with a randomly selected supplementary sample from four county councils and three municipalities consisting of 23,153 men and 28,261 women aged 16-84 years. Mental health problems included; psychological distress (GHQ-12), severe anxiety and use of antidepressant medication. Economic hardship was measured by a combined economic hardships measure including low household income, inability to meet expenses and lacking cash reserves. Results The results from multivariate adjusted (age, country of birth, educational level, occupational status, employment status, family status and long term illness) logistic regression analysis indicate that self-reported current economic difficulties (inability to pay for ordinary bills and lack of cash reserves), were significantly associated with both women's and men's mental health problems (all indicators), while low income was not. In addition, we found a statistically significant graded association between mental health problems and levels of economic hardships. Conclusions The findings indicate that indicators of self-reported current economic difficulties seem to be more strongly associated with poor mental health outcomes than the more conventional measure low income. Furthermore, the likelihood of mental health problems differed significantly in a graded fashion in relation to levels of economic hardships.